DISTRIBUTION OF SINGLE NUCLEOTIDE POLYMORPHISMS (SNPs) OF Y CHROMOSOME HAPLOGROUP O IN VIETNAMESE - Tôn, Nguyễn Đăng (Vietnam Journal of Biotechnology, 2011)
Markers on the non-recombining portion of the human Y chromosome continue to have applications in many fields including evolutionary biology, forensics, medical genetics, and genealogical reconstruction. Vietnam has 54 ethnic nationalities, of which Kinh is the majority with 87% of population. Until now, Y chromosome and mtDNA haplogroups determining patemal and maternal lineages, respectively, in Vietnamese have not been investigated. In this report, we present data on distribution and frequency of Y haplogroups in Kinh ethnic nationality of Vietnam. To investigate a distribution of Y chromosome variation in Kinh ethnic nationality, ten binary markers on the Y chromosome M175, PI86, PI91, PI96, Ml 19, M50, Ml03, MllO, SRY465, JST022454 belonging to haplogroup O, were genotyped by primer extension in 248 normal male samples, collected from North Vietnam provinces. The results showed that six ofthe 10 binary markers gave polymorphisms in the samples. Haplogroup 01a*-M119 was observed with highest frequency (62.9%), while haplogroups 0*-M175/P186/P191/P196 was with 10.1% distribution. Haplogroups 01a2 (M50, M103, and MllO) and 02b-SRY465 were not detected. Taking together, Y chromosome of Vietnamese Kinh ethnic nationality was most frequently distributed in the haplogroup Ola*, followed by haplogroups O*, and 02b. The hap logroup01a2 was not found in the samples investigated.